Dual roles of B lymphocytes in mouse models of diet‐induced nonalcoholic fatty liver disease. Issue 4 (17th March 2022) - Karl, Martin; Hasselwander, Solveig; Zhou, Yawen; Reifenberg, Gisela; Kim, Yong Ook; Park, Kyoung‐Sook; Ridder, Dirk A.; Wang, Xiaoyu; Seidel, Eric; Hövelmeyer, Nadine; Straub, Beate K.; Li, Huige; et al.
Abstract: Background and Aims: Growing evidence suggests an important role of B cells in the development of NAFLD. However, a detailed functional analysis of B cell subsets in NAFLD pathogenesis is lacking. Approach and Results: In wild‐type mice, 21 weeks of high fat diet (HFD) feeding resulted in NAFLD with massive macrovesicular steatosis, modest hepatic and adipose tissue inflammation, insulin resistance, and incipient fibrosis. Remarkably, B null ( JHT ) mice were partially protected whereas B cell harboring but antibody‐deficient IgMi mice were completely protected from the development of hepatic steatosis, inflammation, and fibrosis. The common feature of JHT and IgMi mice is that they do not secrete antibodies, whereas HFD feeding in wild‐type mice led to increased levels of serum IgG2c. Whereas JHT mice have no B cells at all, regulatory B cells were found in the liver of both wild‐type and IgMi mice. HFD reduced the number of regulatory B cells and IL‐10 production in the liver of wild‐type mice, whereas these increased in IgMi mice. Livers of patients with advanced liver fibrosis showed abundant deposition of IgG and stromal B cells and low numbers of IL‐10 expressing cells, compatible with our experimental data. Conclusions: B lymphocytes have both detrimental and protective effects in HFD‐induced NAFLD. The lack of secreted pathogenic antibodies protects partially from NAFLD, whereas the presence of certain B cell subsets provides additional protection. IL‐10–producing regulatory B cells may represent such a protective B cell subset.